Symmetry in Single-Polarization Reflector Impulse Radiating Antennas - Baum, C.E. (Радиофизика и радиоастрономия, 2002)
There are various construction details for reflector impulse-radiating antennas (IRAs) which limit the achievement of the ideal performance characteristics. Symmetry planes are important for polarization purity in the direction of the main beam. This involves details of the feed cables, possible inclusion of a ground plane perpendicular to the ideal electric field, and location of perturbations in low-field regions. Another symmetry concerns the balancing of the low-frequency electric and magnetic dipoles by including special structures connected to the feed arms. В импульсных рефлекторных антеннах (IRAs) имеются различные детали конструкций, которые ограничивают возможность получения идеальных рабочих характеристик. Наличие плоскостей симметрии важно для чистоты поляризации в направлении основного луча. На это влияют детали кабелей питания, возможность включения плоскости земли перпендикулярно идеальному электрическому полю и положение возмущений в затененной области. Другая симметрия связана с уравновешиванием низкочастотных электрических и магнитных диполей за счет включения специальных структур, связанных с фидерными кронштейнами. У імпульсних рефлекторних антенах (IRAs) присутні різні деталі конструкцій, які обмежують можливість отримання ідеальних робочих характеристик. Наявність площин симетрії є важливою для чистоти поляризації у напрямку основного променя. На це впливають деталі кабелів живлення, можливість включення площини землі перпендикулярної ідеальному електричному полю та розміщення збурень у затіненій зоні. Друга симетрія пов’язана з урівноваженням низькочастотних електричних і магнітних диполів за рахунок включення спеціальних структур, пов’язаних з фідерними кронштейнами.